Follow up Study on Outcomes of RT-PCR Positive Patients with COVID-19: A Descriptive Study (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: A considerable part of coronavirus disease 2019 (COVID-19) patients eventually undergo long-lasting symptoms like weakness, breathlessness, myalgia, anxiety and few cognitive dysfunctions for several months after acute infection. As this virus may continue to spread, the follow-up of pulmonary infections with corona virus for extended period of time following involvement of many human systems as well.Objective: To follow up effects of SARS-CoV2 on human body for comprehensive mitigation of all complications.Methods: It is a descriptive type of cross sectional study. Purposive sampling technique was applied from the medical record of Combined Military Hospital (CMH) Dhaka from July 2020 to December 2020. Follow up the necessary datum which was possessed by telephone for the duration six months since the date of discharge by well-structured questionnaire and stored in Statistical Package for the Social Sciences (SPSS) v26 with proper editing and cleaning.Results: Diverse profiles regarding RT-PCR positive cases differed widely during this research. Among 190 respondents, 179(94.21%) patients were symptomatic and 11(05.79%) were asymptomatic. Male patients had a higher portion 133(70.00%) compared to females 46(24.00%) patients among symptomatic groups. The average age of COVID-19 patients was 45.27±14.09. An association had been found between patients with or without clinical manifestations with the habit regarding smoking (p